Preoperative Risk Factors for Complications in Elective Ankle and Hindfoot Reconstruction. Issue 1 (February 2018) - Mulligan, Ryan P.; McCarthy, Kevin J.; Grear, Benjamin J.; Richardson, David R.; Ishikawa, Susan N.; Murphy, G. Andrew
Background . The purpose of this study was to examine medical, social, and psychological factors associated with complications and reoperation after foot and ankle reconstruction. Methods . A retrospective chart review was conducted of 132 patients (135 feet; 139 operative cases) who had elective foot and ankle reconstruction. Medical, social, and psychological variables were documented. Primary outcomes included complications and reoperations. Results . The overall complication rate was 28% (39/139), and the reoperation rate was 17% (24/139). Alcohol use (P = .03) and preoperative narcotic use (P = .02) were risk factors for complications, with delayed wound healing more frequent in alcohol users (P = .03) and deep infection (P = .045) and nonunion (P = .046) more frequent preoperative narcotic use. Deep infection also was more frequent in tobacco users (P < .01). Older patients were less likely to undergo reoperation (risk of reoperation increased with age). Other variables were not associated with increased complications. Conclusion . Patients who consumed alcohol or had been prescribed any amount of narcotic within 3 months preoperatively were at increased risk for complications. Patients who smoked were more likely to have a wound infection. Surgeons should be aware of these factors and counsel patients before surgery. Levels of Evidence: Level III: Retrospective comparative study